Daily Habits and Work-life Boundary Control: Telework in the Era of COVID-19 - Rosengren, Calle; Bäcklander, Gisela; Palm, Kristina (Nordic Journal of Working Life Studies, 2024)
Telework has had a dramatic increase worldwide, especially in the Nordic countries. When work is conducted in the domestic area, the boundaries between work and private life easily become blurred. In this paper, we investigate the daily habits of Swedish municipal office workers as they worked from home during the pandemic with the aim to understand the role of habits in upholding boundaries between work and non-work. Our results indicate that habits from the workplace were sometimes disrupted, and other times transferred to the domestic area. We also saw examples of the establishment of new habits that helped to facilitate role transitions between work and non-work roles, so-called ‘transitional habits’. Our main contribution is to show how the establishment of daily transitional habits can alleviate role shifts and thus help to keep work and non-work roles boundaries separate and distinct.